A “Choose-Your-Own” Classroom-Based Activity That Promotes Scientific Inquiry about RNA Interference - Jeremy L. Hsu (American Society for Microbiology, 2019)
RNA interference (RNAi), the process that results in the degradation of a target gene’s mRNA, is a fundamental part of eukaryotic gene regulation and is also an important molecular technique that allows for experimental manipulation of gene expression without altering DNA sequences. Despite the importance of RNAi, there have been relatively few lecture-based activities designed to teach about the consequences of this process and counter common misconceptions. I present here an inquiry-based activity that is centered around a “choose your own experiment” design where students generate hypotheses and critically evaluate their ideas by choosing several simulated experiments. The activity presents students with one of the original puzzling observations, the discovery that triggering overexpression of a given gene in a flower resulted in an opposite change in phenotype than expected, and the subsequent discovery that there was a dramatic decrease of that gene’s mRNA, that sparked the discovery of RNAi. Students then propose a molecular mechanism for these results before using a limited budget of funding to simulate their choice of experiments. Simulated results are provided for these experiments, and students must work together to interpret and discuss these results before deciding on the next experiment. I provide a guide for instructors on how to implement this activity, with suggestions on how to vary the activity to fit different class sizes as well as an abbreviated version for instructors who are short on time. Finally, I include an aligned assessment so that instructors may check student learning about the impacts of RNAi.